A Novel Vector Control Method of Double PMSM Based on Monolithic DSP Structure - DING Huchen; ZHAN Zhejun; GAO Jinhui; ZHANG Jibin; WANG Qing (机车电传动)
A novel vector control method for driving double PMSM based on one control unit commanding two independent main circuit loops was proposed. Using vector control of the rotor filed oriented, input torque command was given with the maximum torque current control principle to implement double current inner loop. Compared with the original asynchronous slip control system, the new method had the advantages of high control precision, fast dynamic response, more suiting for tram car complex operating conditions, no permanent magnet motor excitation current, and obvious energy-saving.